Access to and quality of sexual and reproductive health services in Britain during the early stages of the COVID-19 pandemic: a qualitative interview study of patient experiences. Issue 1 (20th April 2022) - Bosó Pérez, Raquel; Reid, David; Maxwell, Karen J; Gibbs, Jo; Dema, Emily; Bonell, Christopher; Mercer, Catherine H; Sonnenberg, Pam; Field, Nigel; Mitchell, Kirstin R
Abstract : Introduction: Access to quality sexual and reproductive health (SRH) services remains imperative even during a pandemic. Our objective was to understand experiences of delayed or unsuccessful access to SRH services in Britain during the early stages of the COVID-19 pandemic. Methods: In October and November 2020 we conducted semi-structured telephone interviews with 14 women and six men reporting an unmet need for SRH services in the Natsal-COVID survey, a large-scale quasi-representative web-panel survey of sexual health and behaviour during COVID-19 (n=6654). We purposively sampled eligible participants using sociodemographic quotas. Inductive thematic analysis was used to explore service access and quality and to identify lessons for future SRH service delivery. Results: Twenty participants discussed experiences spanning 10 SRH services including contraception and antenatal/maternity care. Participants reported hesitancy and self-censorship of need. Accessing telemedicine and 'socially-distanced' services required tenacity. Challenges included navigating changing information and procedures; perceptions of gatekeepers as obstructing access; and inflexible appointment systems. Concerns about reconfigured services included reduced privacy; decreased quality of interactions with professionals; reduced informal support; and fewer preventive SRH practices. However, some participants also described more streamlined services and staff efforts to compensate for disruptions. Many viewed positively the ongoing blending of telemedicine with in-person care. Conclusion: The COVID-19 pandemic impacted access and quality of SRH services. Participants' accounts revealed self-censorship of need, difficulty navigating shifting service configurations and perceived quality reductions. Telemedicine offers potential if intelligently combined with in-person care. We offer initial evidence-based recommendations for promoting an equitable restoration and future adaption of services.